Pierre Villard - Sasson, Jack M. (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
He sat by a makeshift desk in a recess of a labyrinthian office on Rue de la Perle in Paris, focusing intently on a small tablet in his left hand, a pencil in his right ready set to transcribe cuneiform onto paper. It was June of ’93 and while it was the first sight I had of Pierre Villard, who passed away much too young this past January, by then he was hardly unknown to me. In 1982, Pierre had joined a Paris équipe (ER 193, headed by Jean-Marie Durand) that was charged with editing a vast treasury of tablets retrieved from Tell Hariri. By the time we met, he had already published several studies on these Mari archives; but for me perhaps none was as arresting as his earliest (1986), a reconstruction of a voyage toward Ugarit that King Zimri-Lim of Mari, with an impressive entourage of thousands, undertook in his 9th and 10th years of rule. The documentation had previously elicited comments (including mine), but Pierre had managed to concretize the event. By placing it on an assured trajectory, he successfully stripped the enterprise from potentially fanciful explanations. Over several lunch breaks, I got to know Pierre a little. Reticent at first (perhaps taken aback by my frontal ways), he gradually revealed tidbits about himself and his interests. Born in the summer of ’58, Pierre had lost his father when still in his early teens. Within a few years he had become hooked on Assyriology in the classrooms of Paul Garelli and Dominique Charpin. A two-year stint (1983-85) teaching in Latakia and traveling in the Levant gave him a physical sense of the world he was researching. Interest piqued, he eventually specialized in two distinct periods of Mesopotamian cultures, albeit almost a full millennium apart: Those of the Mari age and of the Neo-Assyrian empire. Pierre defended his Ph.D in 1986, submitting a thesis on L’esprit de cour et le style des courtisans dans l’Assyrie des Sargonides. Two years later, he was elected “Maître assistant” in Paris 1 Panthéon-Sorbonne University. Pierre matured as a researcher and educator at several academic institutions, but especially as a member of équipe HAROC (Nanterre). When in 2000 he defended his accreditation to supervise research (HDR), he prepared a superb study on each of his two specialties: on the rhetoric adopted by Neo-Assyrian courtiers and on the administration of Mari under Yasmah-Addu (eventually published in Amurru 2 of 2002). The latter was strikingly original in discriminating between those managing the private estates of Yasmah-Addu, in Mari as well as beyond it, and those who oversaw affairs of state, mostly on behalf of the king’s father, the redoubtable Samsi-Addu. As editor of a reference work (Civilizations of the Ancient Near East, 1995), I had welcomed an earlier vision of this account in a compelling portrait of an empire “with three heads,” at Shubat-Enlil (Samsi-Addu), Ekallatum (Ishme-Dagan) and Mari (Yasmah-Addu). By the turn of the millennium, Pierre had been recruited to what is now Université Clermont Auvergne where he played a role in shaping a program that supported Assyriology, a professional degree that was hitherto available elsewhere only in Paris, Lille, Lyon, and Strasbourg. He penned a stream of important publications (alas for me based almost exclusively on first millennium documents) that contributed insightfully on a broad range of themes associated with the Assyrian empire, its administration, its military establishment, and its architectural ingenuity. He also delved profitably into the many facets of its juridical system. The hallmarks of Pierre’s craft include choreography of details, gleanings from neglected notices, ingenious musings over the evidence, and startlingly convincing conclusions. At the same time, Pierre was welcomed into several projects and organizations at other universities, among them in Lyon. He also participated in juries evaluating theses for advanced degrees. In his last weeks among us, Pierre was putting the final touches on a Rapport d’activités that included a review of his past scholarly and university achievements as well as an outline of projects he wished to undertake. For him, his mission on earth had yet to be complete. Sadly, as he penned his commitment to preparing the next generation of scholars, Pierre lost his fight against a cruel disease: Fate had interfered, clipping a paragraph in mid-formation and, with it as well, a career well spent but also with so much more to give. Pierre leaves many whom he loved and who loved him, among them Laura Battini who is now charged with the sad task of editing several unpublished works. He is mourned by three grieving children, Élisabeth (1998-), Lorenzo (2000-), and Matthieu (2002-), his sister Françoise (Aellen) and her entire family, several kinfolks, and numerous saddened colleagues. “May his memory be a blessing”. [Readers of this obituary may want also to read the posting at https://archeorient.hypotheses.org/22309.]